Elemental Analysis of Tobacco Leaves by FAAS and WDXRF Spectroscopy - CAMAS, NECDET; ARSLAN, BURHAN; UYANIK, AHMET (Asian Journal of Chemistry, 2010)
The intensity of the different elements in tobacco leaves was comparatively determined by using flame atomic absorption (FAAS) and wavelength dispersive X-ray florescence (WDXRF) methods. The accuracy of both methods was evaluated by the data obtained from standard reference materials (CRMs), tobacco leaves of CTA-OTL-1 (oriental tobacco leaves) and CTA-VTL-2 (virginia tobacco leaves). The results were in good agreement with the literature values. The WDXRF method is also found most suitable and easily applicable to the analysis of tobacco leaves. Besides the elemental content, the highest quality of tobacco type cultivated in Turkey was determined in accordance with the nicotine and the reducing sugar content.